Indomethacin Increases Neurogenesis across Age Groups and Improves Delayed Probe Trial Difference Scores in Middle-Aged Rats - McGuiness, James A.; Scheinert, Rachel B.; Asokan, Aditya; Stadler, Vivien-Charlott; Lee, Christian S.; Rani, Asha; Kumar, Ashok; Foster, Thomas C.; Ormerod, Brandi K. (Frontiers in Aging Neuroscience, 2017)
We tested whether indomethacin or rosiglitazone treatment could rejuvenate spatial ability and hippocampal neurogenesis in aging rats. Young (4 mo; n = 30), middle-aged (12 mo; n = 31) and aged (18 mo; n = 31) male Fischer 344 rats were trained and then tested in a rapid acquisition water maze task and then fed vehicle (500µl strawberry milk), indomethacin (2.0mg/ml) or rosiglitazone (8.0mg/ml) twice daily for the remainder of the experiment. A week after drug treatment commenced, the rats were given 3 daily BrdU (50mg/kg) injections to test whether age-related declines in neurogenesis were reversed. One week after the final BrdU injection (~2.5 weeks after the 1st water maze session), the rats were trained to a find novel hidden water maze platform location, tested on 15min and 24h probe trials and then killed 24h later. During the first water maze session, young rats outperformed aged rats but all rats learned information about the hidden platform location. Middle-aged and aged rats exhibited better memory probe trial performances than young rats in the 2nd water maze session and indomethacin improved memory probe trial performances on the 2nd versus 1st water maze session in middle-aged rats. Middle-aged rats with more new neurons had fewer phagocytic microglia and exhibited better hidden platform training trial performances on the 2nd water maze session. Regardless of age, indomethacin increased new hippocampal neuron numbers and both rosiglitazone and indomethacin increased subependymal neuroblasts/neuron densities. Taken together, our results suggest the feasibility of studying the effects of longer-term immunomodulation on age-related declines in cognition and neurogenesis.